Studies on the genus Capparis L. (Capparaceae) in Lao PDR. Issue 2 (2nd July 2016) - Fici, Silvio
Abstract : Southeastern Asia is one of the main centres of diversity of the genus Capparis in the Old World. Morpho-chorological investigations carried out on collections from Lao PDR provided new data on the variation and distribution of some intrageneric taxa that were critical, poorly known or unrecorded in the country. The variability of Capparis pyrifolia and Capparis zeylanica is discussed, while Capparis acutifolia subsp . acutifolia and Capparis tenera are respectively confirmed and first recorded in Lao PDR. A new variety of Capparis micracantha is described and 12 lectotypes are designated. For each taxon morphological, chorological and autecological data are given.